Improvement By Using Antifouling On Retaining Wall - Marzuki, Kamal Khairi Ahmad (Universiti Sains Malaysia, 2021)
Microorganisms are recognized to be present in nearly every environmental situation. Microorganisms create aggressive metabolites such as acids, carbon dioxide, and sulfur compounds, which can cause irreversible damage. A superhydrophobic coating is a low-energy surface layer that easily repels water. The surface topography and chemistry are critical for a surface to acquire the hydrophobic property. The objective of this study is to determine the characteristic of antifouling and to evaluate the performance of antifouling on grout, mortar, and reinforced mortar cubes. Tests conducted were water contact angle (WCA), sliding angle (SA), peel-off test, and fungi resistance test. The results for WCA for grout was 123.0˚, the mortar was 138.6˚, and reinforced mortar was 131.4˚ which were lower than 150˚. The results for SA for grout was 70 ± 5˚, the mortar was 50 ± 5˚, and reinforced mortar was 15 ± 5˚ which were higher than 10˚. Therefore, the coating does not possess superhydrophobicity behavior. Peel off test was conducted to replicate the effect of mechanical scratch. All of the samples experienced decreased performance as the WCA of grout decrease into 124.6˚ to 102.8˚ to 87.4˚ while WCA of mortar decrease to 120.8˚ to 104.5˚ to 83.4˚ and the WCA of reinforced mortar decrease to 122.2˚ to 112.0˚ to 83.2˚. The fungi resistance test shows that fungi colonized both uncoated and coated samples for all types of samples after 90 days of observation. This study can be summarised that the coating does not achieve superhydrophobicity.